MgAl2O4 spinel coating on titanium and titanium alloy surface and preparation method thereof
By depositing MgAl2O4 spinel coating on the surface of titanium and titanium alloys, the problem of poor high-temperature performance of titanium and titanium alloys is solved, and higher high-temperature mechanical properties and corrosion resistance are achieved, while reducing production costs and cycles.
Patent Information
- Application Number
- CN202310466189.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-04-27
AI Technical Summary
The poor high-temperature performance of titanium and titanium alloys limits the possibility of long-term use in aircraft engines.
The MgAl2O4 spinel coating was deposited on the surface of titanium or titanium alloy workpieces by hot-dip plating, and prepared by hot-dip plating, oxidation treatment and vacuum diffusion annealing of Al-Mg intermediate alloys.
It significantly improves the high-temperature performance of titanium and titanium alloys, enhances its mechanical properties and corrosion resistance at high temperatures, and reduces production costs and cycles.
Smart Images

Figure HDA0004202341680000011 
Figure HDA0004202341680000012 
Figure HDA0004202341680000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium and titanium alloy surface coating preparation, and in particular to a MgAl2O4 spinel coating on the surface of titanium and titanium alloy and a preparation method thereof. Background Art
[0002] Titanium and its alloys, with their advantages of high specific strength, low density, excellent corrosion resistance, and stable performance at medium temperatures, are widely used in a wide range of fields, including aerospace, military, automotive manufacturing, and the chemical industry. In particular, with the improvement of aircraft performance and the increase in thrust-to-weight ratio of aircraft engines, titanium and its alloys have become particularly attractive in aircraft engines. However, the poor high-temperature performance of titanium and its alloys has limited their further application as high-temperature components in aircraft engines. In other words, the long-term use of titanium and its alloys in aircraft engines depends on their high-temperature performance. One of the most ideal and effective methods to improve the high-temperature performance of titanium and its alloys is surface coating modification.
[0003] MgAl2O4 spinel has a high melting point, high hardness, and low density. It exhibits high mechanical strength at both room and elevated temperatures, excellent corrosion resistance to chemical attack, a low coefficient of thermal expansion, and good thermal shock resistance. Solid-phase synthesis is commonly used in industry to produce MgAl2O4 spinel, but this synthesis requires relatively high temperatures, ranging from 1300–1800°C. MgAl2O4 spinel has also been demonstrated to be an effective reinforcing agent for various composite materials, improving their hardness, fracture toughness, wear resistance, and high-temperature performance. Due to these advantages, MgAl2O4 spinel has been widely used in applications such as steel ladles, cement rotary kilns, catalyst supports, infrared windows, and optical lenses. However, there are currently few reports on the application of MgAl2O4 spinel in metal surface coatings, particularly those on titanium and titanium alloys. Summary of the Invention
[0004] Based on the technical problems mentioned in the background art, the present invention aims to solve the problem of poor high-temperature performance of existing titanium and titanium alloys and to increase the operating temperature of titanium and titanium alloys. The present invention provides a MgAl2O4 spinel coating on the surface of titanium and titanium alloys and a preparation method thereof, which has the advantages of low cost, short cycle time, easy production and processing, good controllability, excellent mechanical properties, and excellent high-temperature performance.
[0005] The present invention provides a method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloys, comprising the following steps:
[0006] (1) The surface of the titanium or titanium alloy workpiece is polished and cleaned and dried; under the condition of passing protective gas, the titanium or titanium alloy workpiece is immersed in molten Al-Mg master alloy for hot dip plating;
[0007] The shielding gas is a mixed gas of SF6 and CO2, with SF6 accounting for 4% of the total gas; the Mg content of the Al-Mg master alloy is 4% to 8%.
[0008] The hot-dip coating temperature is 700°C and the hot-dip coating time is 20 min;
[0009] (2) extracting the workpiece from step (1) from the graphite crucible, removing excess liquid from the surface, quenching with water, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0010] (3) oxidizing the workpiece obtained in step (2) in oxygen to obtain a workpiece having a mixed oxide layer of Al2O3 and MgO on the surface;
[0011] The oxidation temperature is 300°C and the oxidation time is 2h;
[0012] (4) Spraying the fluoride salt aqueous solution on the surface of the workpiece in step (3) to obtain an oxidized coating workpiece with fluoride salt deposited on the surface:
[0013] The fluoride salt is one or a combination of K3AlF6, Na3AlF6, Li3AlF6, NaF, LiF, KF, the concentration of the fluoride salt aqueous solution is 0.5wt% to 3wt%, and the fluoride salt deposition amount on the workpiece surface is 3mg / cm 2 .
[0014] (5) The workpiece in step (4) is subjected to vacuum diffusion annealing treatment to obtain a MgAl2O4 spinel coating on the surface of the titanium or titanium alloy workpiece.
[0015] The vacuum diffusion annealing temperature is 750-950°C, and the vacuum diffusion annealing time is 5-20h. If the annealing temperature exceeds 950°C, it will cause "abnormal" coarsening of the grains and affect the mechanical properties of the entire alloy.
[0016] The method for preparing the MgAl2O4 spinel coating on the surface of titanium and titanium alloys of the present invention has the following beneficial effects:
[0017] (1) The hot-dip coating process is low-cost and provides good adhesion between the coating and the substrate. The coating composition can be controlled by controlling the Mg content of the Al-Mg master alloy.
[0018] (2) The oxidation and vacuum annealing process has no requirements on the size or shape of the workpiece and is simple and easy to operate. The particle size and amount of MgAl2O4 spinel in the coating can be controlled by controlling the vacuum annealing temperature.
[0019] (3) Compared with conventional metal-based coatings and ceramic coatings on titanium and titanium alloy surfaces, the MgAl2O4-containing spinel coating prepared by the present invention combines the good adhesion of metal-based coatings with the high-temperature stability of ceramic-based coatings, which can greatly improve the high-temperature performance of titanium and titanium alloys. This is of great significance for promoting the application of titanium and titanium alloys in the aviation industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a surface microstructure diagram of a workpiece having a MgAl2O4 spinel coating obtained in Example 1;
[0021] Figure 2 This is a surface microstructure diagram of a workpiece having a MgAl2O4 spinel coating obtained in Example 2;
[0022] Figure 3 This is a surface microstructure of a workpiece having a MgAl2O4 spinel coating obtained in Example 3;
[0023] Figure 4 This is a surface microstructure of a workpiece having a MgAl2O4 spinel coating obtained in Example 4;
[0024] Figure 5 This is a surface microstructure diagram of a workpiece having a MgAl2O4 spinel coating obtained in Example 5;
[0025] Figure 6 This is a surface microstructure of a workpiece having a MgAl2O4 spinel coating obtained in Example 6;
[0026] Figure 7 This is the XRD pattern of the workpiece surface with MgAl2O4 spinel coating prepared in Example 1;
[0027] Figure 8 The hardness variation curves of the workpieces obtained in Comparative Example 1, Comparative Example 2 and Example 4 are shown;
[0028] Figure 9 The following is a graph showing the oxidation weight gain curves of the workpieces obtained in Comparative Example 1, Comparative Example 2 and Example 4. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings. The described embodiments are only embodiments of a part of this application, and these embodiments are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] Comparative Example 1
[0031] Three uncoated TC4 titanium alloy workpieces were selected, their hardness was measured and the average hardness was 195HV. Fifteen uncoated TC4 titanium alloy workpieces were selected for continuous air oxidation experiments at 900℃. A sample was taken out every 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, 125, and 150 hours to measure the oxidation weight gain. The oxidation weight gain of the sample after 150 hours was 142mg / cm 2 .
[0032] Comparative Example 2
[0033] (1) The surface of the TC4 titanium alloy workpiece was polished and cleaned and dried, and the workpiece was immersed in molten pure aluminum for hot dip plating; the hot dip temperature was 700 °C and the hot dip time was 20 min;
[0034] (2) extracting the workpiece in step (1) from the molten pure aluminum, removing excess liquid phase from the surface, quenching with water, and drying to obtain a hot-dip aluminum-coated workpiece;
[0035] (3) Select three workpieces from step (2), measure their hardness and take the average hardness, the average hardness is 118HV; select 11 workpieces from step (2) and conduct a continuous air oxidation test at 900℃, take out a sample every 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, 125, and 150 hours to measure the oxidation weight gain, the oxidation weight gain of the sample after 150 hours is 115mg / cm 2 .
[0036] Comparative Example 3
[0037] (1) The surface of the TC4 titanium alloy workpiece was polished and cleaned and dried. The TC4 titanium alloy workpiece was immersed in molten Al-4Mg master alloy for hot dip coating under the condition of passing 4% SF6 and 96% CO2 mixed gas. The hot dip temperature was 700℃ and the hot dip time was 20min.
[0038] (2) extracting the workpiece in step (1) from the molten Al-4Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0039] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0040] (5) The workpiece in step (4) is subjected to vacuum diffusion annealing treatment at 850°C for 10 hours, and the surface of the TC4 titanium alloy workpiece is still a mixed oxide layer of Al2O3 and MgO.
[0041] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 167HV; select the workpiece from step (2) and conduct a continuous air oxidation test at 900℃. The weight gain of the sample after 150 hours of oxidation is 101mg / cm 2 .
[0042] Example 1
[0043] (1) The surface of the TC4 titanium alloy workpiece was polished and cleaned and dried. The TC4 titanium alloy workpiece was immersed in molten Al-4Mg master alloy for hot dip coating under the condition of passing 4% SF6 and 96% CO2 mixed gas. The hot dip temperature was 700℃ and the hot dip time was 20min.
[0044] (2) extracting the workpiece in step (1) from the molten Al-4Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0045] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0046] (4) Spraying a 1 wt% LiF aqueous solution on the surface of the workpiece in step (3) to obtain an oxidation coating workpiece with LiF deposited on the surface: the amount of fluoride salt deposited on the surface of the workpiece is 3 mg / cm 2 ;
[0047] (5) performing vacuum diffusion annealing on the workpiece in step (4) at 850° C. for 10 h to obtain a MgAl 2 O 4 spinel coating on the surface of the TC4 titanium alloy workpiece;
[0048] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 234HV; select the workpiece from step (2) and conduct a continuous air oxidation test at 900℃. The weight gain of the sample after 150 hours of oxidation is 12.03mg / cm 2 .
[0049] Example 2
[0050] (1) The surface of the TC4 titanium alloy workpiece was polished and cleaned and dried. The TC4 titanium alloy workpiece was immersed in molten Al-6Mg master alloy for hot dip coating under the condition of passing 4% SF6 and 96% CO2 mixed gas. The hot dip temperature was 700℃ and the hot dip time was 20min.
[0051] (2) extracting the workpiece in step (1) from the molten Al-6Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0052] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0053] (4) Spraying a 1 wt% LiF aqueous solution on the surface of the workpiece in step (3) to obtain an oxidation coating workpiece with LiF deposited on the surface: the amount of fluoride salt deposited on the surface of the workpiece is 3 mg / cm 2 ;
[0054] (5) The workpiece in step (4) is subjected to vacuum diffusion annealing at 850° C. for 10 h to obtain a MgAl2O4 spinel coating on the surface of the TC4 titanium alloy workpiece. Compared with Example 1, the MgAl2O4 spinel content on the workpiece surface is increased;
[0055] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 261HV; select the workpiece from step (2) and conduct a continuous air oxidation test at 900℃. The weight gain of the sample after 150 hours of oxidation is 8.39mg / cm 2 .
[0056] Example 3
[0057] (1) The surface of the TC4 titanium alloy workpiece was polished, cleaned, and dried. The TC4 titanium alloy workpiece was immersed in molten Al-8Mg master alloy for hot dip coating under the condition of a mixture of 4% SF6 and 96% CO2. The hot dip temperature was 700°C and the hot dip time was 20 min.
[0058] (2) extracting the workpiece in step (1) from the molten Al-8Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0059] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0060] (4) Spraying a 1 wt% LiF aqueous solution on the surface of the workpiece in step (3) to obtain an oxidation coating workpiece with LiF deposited on the surface: the amount of fluoride salt deposited on the surface of the workpiece is 3 mg / cm 2 ;
[0061] (5) The workpiece in step (4) was subjected to vacuum diffusion annealing at 850° C. for 10 h to obtain a MgAl 2 O 4 spinel coating on the surface of the TC4 titanium alloy workpiece. Compared with Example 2, the MgAl 2 O 4 spinel content on the workpiece surface was reduced;
[0062] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 249HV; select the workpiece from step (2) and conduct a continuous air oxidation test at 900℃. The weight gain of the sample after 150 hours of oxidation is 10.97mg / cm 2 .
[0063] Example 4
[0064] (1) The surface of the TC4 titanium alloy workpiece was polished and cleaned and dried. The TC4 titanium alloy workpiece was immersed in molten Al-6Mg master alloy for hot dip coating under the condition of passing 4% SF6 and 96% CO2 mixed gas. The hot dip temperature was 700℃ and the hot dip time was 20min.
[0065] (2) extracting the workpiece in step (1) from the molten Al-6Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0066] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0067] (4) Spraying a 1 wt% LiF aqueous solution on the surface of the workpiece in step (3) to obtain an oxidation coating workpiece with LiF deposited on the surface: the amount of fluoride salt deposited on the surface of the workpiece is 3 mg / cm 2 .
[0068] (5) The workpiece in step (4) was subjected to vacuum diffusion annealing at 950° C. for 10 h to obtain a MgAl 2 O 4 spinel coating on the surface of the TC4 titanium alloy workpiece. Compared with Example 2, the average particle size of the MgAl 2 O 4 spinel on the surface of the workpiece was increased.
[0069] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 286HV; select 11 workpieces from step (2) and conduct a continuous air oxidation experiment at 900℃, take out a sample every 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, 125, 150 hours to measure the oxidation weight gain, the oxidation weight gain of the sample after 150 hours is 7.64mg / cm 2 .
[0070] Example 5
[0071] (1) The surface of the TC4 titanium alloy workpiece was polished and cleaned and dried. The TC4 titanium alloy workpiece was immersed in molten Al-6Mg master alloy for hot dip coating under the condition of passing 4% SF6 and 96% CO2 mixed gas. The hot dip temperature was 700℃ and the hot dip time was 20min.
[0072] (2) extracting the workpiece in step (1) from the molten Al-6Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0073] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0074] (4) Spraying a 1 wt% LiF aqueous solution on the surface of the workpiece in step (3) to obtain an oxidation coating workpiece with LiF deposited on the surface: the amount of fluoride salt deposited on the surface of the workpiece is 3 mg / cm 2 .
[0075] (5) The workpiece in step (4) was subjected to vacuum diffusion annealing at 750° C. for 10 h to obtain a MgAl 2 O 4 spinel coating on the surface of the TC4 titanium alloy workpiece. Compared with Example 2, the average particle size of the MgAl 2 O 4 spinel on the surface of the workpiece was reduced.
[0076] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 252HV; select the workpiece from step (2) and conduct a continuous air oxidation test at 900℃. The weight gain of the sample after 150 hours of oxidation is 8.71mg / cm 2 .
[0077] Example 6
[0078] (1) The surface of the TC4 titanium alloy workpiece was polished, cleaned, and dried. The TC4 titanium alloy workpiece was immersed in molten Al-8Mg master alloy for hot dip coating under the condition of a mixture of 4% SF6 and 96% CO2. The hot dip temperature was 700°C and the hot dip time was 20 min.
[0079] (2) extracting the workpiece in step (1) from the molten Al-8Mg master alloy, removing excess liquid phase from the surface, water quenching, and drying to obtain a hot-dip Al-Mg coated workpiece;
[0080] (3) oxidizing the workpiece in step (2) in oxygen at a temperature of 300° C. for 2 h to obtain a workpiece having a mixed oxide layer of Al 2 O 3 and MgO on the surface;
[0081] (4) Spraying a 1 wt% NaF aqueous solution on the surface of the workpiece in step (3) to obtain an oxidation coating workpiece with NaF deposited on the surface: the amount of fluoride salt deposited on the surface of the workpiece is 3 mg / cm 2 .
[0082] (5) The workpiece in step (4) was subjected to vacuum diffusion annealing at 850° C. for 10 h to obtain a dense MgAl 2 O 4 spinel coating on the surface of the TC4 titanium alloy workpiece. Compared with Example 2, the content and particle size of the MgAl 2 O 4 spinel coating on the workpiece surface were not much different.
[0083] (6) Select three workpieces from step (5), measure their hardness and take the average hardness, the average hardness is 260HV; select the workpiece from step (2) and conduct a continuous air oxidation test at 900℃. The weight gain of the sample after 150 hours of oxidation is 8.36mg / cm 2 .
Claims
1. A method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloys, characterized in that: The preparation method steps are as follows: (1) Grind the surface of the titanium or titanium alloy workpiece flat and clean and dry it; immerse the workpiece in molten Al-Mg master alloy for hot dip plating under the condition of passing protective gas; (2) extracting the workpiece of step (1) from the molten Al-Mg master alloy, shaking off the excess liquid phase on the surface, quenching with water, and drying to obtain a hot-dip Al-Mg coated workpiece; (3) oxidizing the workpiece in step (2) in oxygen to obtain an oxidized coating workpiece having Al2O3 and MgO; (4) Spraying the fluoride salt aqueous solution on the surface of the workpiece in step (3) to obtain an oxidized coating workpiece with fluoride salt deposited on the surface: (5) The workpiece of step (4) is subjected to vacuum diffusion annealing treatment to obtain a MgAl2O4 spinel coating on the surface of the titanium or titanium alloy workpiece.
2. The method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloys according to claim 1, characterized in that: In step (1), the protective gas is a mixed gas of SF6 and CO2, SF6 accounts for 4% of the total gas; the Mg content in the Al-Mg master alloy is 4% to 8%.
3. The method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloy according to claim 1, characterized in that: In step (1), the hot-dip coating temperature is 700° C. and the hot-dip coating time is 20 min.
4. The method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloys according to claim 1, characterized in that: In step (3), the oxidation temperature is 300° C. and the oxidation time is 2 h.
5. The method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloy according to claim 1, characterized in that: In step (4), the fluoride salt is one or a combination of K3AlF6, Na3AlF6, Li3AlF6, NaF, LiF, and KF.
6. The method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloy according to claim 1, characterized in that: The concentration of the fluoride salt aqueous solution in step (4) is 0.5wt%~3wt%, and the surface fluoride salt deposition amount is 3mg / cm 2 .
7. The method for preparing a MgAl2O4 spinel coating on the surface of titanium and titanium alloy according to claim 1, characterized in that: The vacuum diffusion annealing temperature of step (5) is 750-950°C, and the vacuum diffusion annealing time is 5-20h.
Citation Information
Patent Citations
Method of vibration damping in metallic articles
US20040096332A1
Cited By
A method for in-situ preparation of multiphase ceramic composite coating containing MgAlON on a titanium alloy surface by slurry sintering
CN122669381A